ANALISIS PARTISIPASI MASYARAKAT DAN KAPASITAS KELEMBAGAAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM MITIGASI BENCANA BANJIR DI KAWASAN DATARAN TINGGI DIENG - Yogi Risma Listiana; Hendra Try Ardianto (Journal of Politic and Government Studies, 2026)
The Dieng Plateau area is highly vulnerable to hydrometeorological disasters, particularly flooding, due to its geographical conditions, high rainfall, and land-use changes. In disaster mitigation, the role of local government institutions, especially the Regional Disaster Management Agency (BPBD), along with community participation, is crucial. This study aims to analyze the institutional capacity of BPBD Wonosobo Regency and community participation in flood mitigation using a descriptive qualitative method through interviews, observations, and documentation. The results show that BPBD Wonosobo has an adequate institutional framework, including organizational structure, programs, and procedures. However, its implementation still faces challenges such as limited budget, human resources, and suboptimal cross-sector coordination. Meanwhile, community participation is evident in activities such as mutual cooperation and disaster preparedness, although it remains limited and not yet systematically organized. Therefore, strengthening institutional capacity and enhancing community empowerment are necessary to achieve more effective and sustainable flood mitigation efforts.